Self-generating current skin patch containing biodegradable metal

By using biodecomposition metal autogenerating current technology and microneedle structure in skin patches, the problems of low absorption rate and insufficient transmission efficiency of existing skin patches are solved, and efficient transfer of active ingredient and skin repair effects are achieved.

CN119894572APending Publication Date: 2025-04-25LABNPEOPLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066675.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-18
Filing Date
2023-09-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing skin patches have limitations in improving the absorption of active ingredients, and traditional methods such as injection and application dosage forms have problems with pain, inconvenience and side effects.

Method used

Self-generating skin patches containing biodegradable metals are used, which generate microcurrents through the redox potential difference between heterogeneous metals, improve the transfer efficiency of active ingredients by ionic electrophoresis, and enhance the drug delivery effect through microneedle structure and decomposition products.

Benefits of technology

It realizes a skin patch that generates microcurrent without a battery, significantly improves the skin absorption rate and transmission depth of the active ingredients, and has the effect of restoring nerve, muscle, and tissue damage and reducing pain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894572A_ABST
    Figure CN119894572A_ABST
Patent Text Reader

Abstract

The self-generating current skin patch of the present invention comprises: a first region in contact with the skin of a user; and a second region spaced apart from the first region and in contact with an adjacent skin of the skin in contact with the first region, the first region or the second region comprising a biodegradable metal; a first electrode layer formed integrally with the first region in a sheet-like form in direct contact with the skin of the user, and having at least one through-hole; a second electrode layer which is made of a different substance having a standard reduction potential different from that of the substance forming the first electrode layer, is positioned on the skin-contact-opposite side of the first electrode layer in a state insulated from the first electrode layer, and is electrically connected to the second region by at least a portion thereof being extended; and a carrier layer which is positioned on the skin-contact opposite side of the first electrode layer in the form of a sheet having a thickness, is made of a hydrophilic material capable of carrying an ionic solution, and can provide sufficient active ingredient ion electrophoresis and other microcurrent effects by means of a self-generated microcurrent even without a separate power supply device such as a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a skin patch for delivering cosmetic or medicinal active ingredients into the body, and more particularly to a self-generated current skin patch containing a biodegradable metal, which can generate microcurrent when applied to the skin based on the redox potential difference between heterogeneous metals caused by an ion solution composed of or mixed with the active ingredients, and produces beneficial effects through the decomposition of the biodegradable metal in the contact area. Background Art

[0002] Generally speaking, among transdermal methods for supplying active ingredients into the body through the skin, the most common method is to apply a dosage form of a cream or gel-textured product containing the active ingredients to the skin surface. However, compared with the amount applied, a considerable amount of the active ingredients cannot penetrate into the tissue and are wasted. In particular, when the three-dimensional size of the active ingredients such as high molecular weight materials is large, most of them cannot pass through the epidermis of the skin, and cannot even pass through the stratum corneum.

[0003] The most direct percutaneous way to solve this problem is to inject the active ingredients. Although this method directly injects drugs into the body by inserting a needle into the skin and is quickly absorbed in the tissue, it has the advantage of immediate effect. However, the problem is that it can only be injected by experts (self-injection is difficult), and usually uses a needle that is more than ten millimeters long and several millimeters in diameter. Due to the pain of injection, patient compliance is poor.

[0004] In order to minimize the side effects and disadvantages, a drug delivery system based on transdermal administration is being actively developed.

[0005] As mentioned above, active ingredients absorbed through the skin are usually formulated in the form of liquids, creams, gels, etc. Liquids, creams, and gels are difficult to adjust in terms of formulation characteristics, and there are problems with viscosity or contamination of the coating layer.

[0006] Therefore, a method is being adopted in which a patch containing an active ingredient is attached to the skin and the active ingredient is absorbed through the skin.

[0007] The use of active ingredient administration methods such as drugs using patches is increasing because the drugs are absorbed through the skin, which can prevent side effects caused by oral drugs, such as gastrointestinal disorders and dietary effects, and can eliminate the pain and inconvenience of injections.

[0008] Patches are roughly classified into a drug-impermeable backing layer through which the active drug cannot pass, a drug-permeable membrane with drug permeability, and an adhesive layer that allows the patch to adhere to the skin. A storage space for storing the drug is provided between the backing layer and the drug-permeable membrane.

[0009] A major disadvantage of this patch is that due to the low absorption rate of the active ingredient through the skin, it is necessary to reduce the function of the skin permeability barrier, and the absorption rate through the patch is about 20%.

[0010] In order to improve the skin absorption rate of active ingredients such as drugs, various methods are being used. For example, chemical methods such as the use of skin absorption enhancers and the use of prodrugs and physical methods such as iontophoresis and electrophoresis are widely known.

[0011] However, even with these known methods, there are still limitations in increasing the absorption rate of the active ingredient to a satisfactory level, and therefore in order to increase the effect, it is necessary to use more active ingredients than actually required in consideration of the absorption rate.

[0012] In particular, the type of skin absorption enhancer is determined by the design form of the preparation to be used or the physicochemical properties of the constituent components. In order to show the effect, a concentration above a certain level is required. The disadvantage of adding a skin absorption enhancer is that it is difficult to prevent crystallization over time, and the adhesive properties such as adhesion and cohesion change, making it unsuitable for use.

[0013] In addition, regarding the technology that utilizes electricity, since the patch must have a battery, electrodes, circuits and other components, the product structure becomes complicated, resulting in an increase in size, which is not only expensive, but also will generate a large amount of waste after use.

[0014] The applicant has been continuously researching and developing the technology of microneedle patches made of biodegradable metals as a transdermal active ingredient delivery system, and has disclosed technologies that improve the efficiency of transdermal active ingredient delivery and produce beneficial effects during the self-decomposition process through patent registration No. 2114472 "Microneedles using biodegradable metals" and patent registration No. 2291392 "Composite microneedles".

[0015] These technologies have provided excellent transdermal drug delivery methods without stimulating the human pain nerves, through microneedles that can effectively penetrate the stratum corneum and epidermis, and characteristic structures such as multiple microneedles arranged around holes. However, the applicant did not stop there and further researched and developed a method for delivering active ingredients deep into the skin in a short period of time, thereby completing the present invention.

[0016] Therefore, the applicant has proposed the present invention to solve the above-mentioned problems. The related prior art documents are Korean registered patent No. 10-1423241 "Microcurrent generating patch", Korean registered patent No. 10-2390735 "Microcurrent generating patch for transdermal drug delivery and its manufacturing method", etc., but No. 10-1423241 only records the composition and effect of metabolism of the affected part and promotion of blood circulation generated by the microcurrent generated by the metal and gel-like adhesive layer of different materials. Although No. 10-2390735 adopts a drug penetration structure based on an ion carrier method, it only suggests the conceptual structure of the ion carrier patch. As to whether the self-generated electricity without an additional power source can achieve a sufficient ion carrier effect, no specific countermeasures are proposed, and no optimal structure of microneedles composed of biodegradable metals that can be decomposed in the body and the synergistic effect produced thereby are proposed. Summary of the invention

[0017] Technical issues to be solved

[0018] The present invention is used to solve the above-mentioned problems, and its purpose is to provide a self-generated current skin patch containing biodegradable metals, which can generate microcurrent without the need for additional power supply devices such as batteries, thereby maximizing the in vivo delivery effect of active ingredients based on ion electrophoresis, and at the same time achieving the microcurrent effect of restoring damage to nerves, muscles, and tissues and alleviating pain.

[0019] In addition, the purpose of the present invention is to provide a self-generated current skin patch, in which the electrodes and skin contact parts are made of the biodegradable metal with a specific composition of the present invention, and the decomposition products and hydrogen released during decomposition have skin improvement effects and drug delivery enhancer effects.

[0020] In addition, the purpose of the present invention is to provide a self-generated current skin patch, which not only improves the keratin transmittance caused by microneedles in the user's skin contact part, but also reduces the skin resistance value of the applicable part, and significantly improves the in vivo delivery effect of the active ingredient based on ion electrophoresis.

[0021] Means of solving the problem

[0022] To achieve the aforementioned objectives, the self-generated current skin patch of the present invention comprises: a first area contacting the user's skin and a second area separated from the first area and contacting adjacent skin that contacts the first area, the first area or the second area comprising a biodegradable metal that contacts the user's skin or reacts with moisture in the tissue to be decomposed and absorbed; a first electrode layer, which is formed integrally with the first area in the form of a thin sheet that directly contacts the user's skin, and has at least one through portion that can transmit fluid from the opposite side of the skin contact; a second electrode layer, which is composed of a heterogeneous substance having a standard reduction potential different from that of the substance forming the first electrode layer, is located on the opposite side of the skin contact of the first electrode layer in an insulated state from the first electrode layer, and at least a portion is extended and electrically connected to the second area; a carrying layer, which is located on the opposite side of the skin contact of the first electrode layer in the form of a sheet with thickness, and is composed of a hydrophilic material that can carry ionic solutions.

[0023] The first area or the second area may include at least one microneedle protruding in a direction of contacting the user's skin.

[0024] The biodegradable metal may be represented by the following Chemical Formula 1.

[0025] [Chemical formula 1]

[0026] Mg a Zn b Ca c X d

[0027] (In Chemical Formula 1, a, b, c and d are weight % of each component, a+b+c+d=100 weight %, a is the largest, 0≤b≤5, 0≤c≤1, 0≤d≤1, and X is one or more impurity groups consisting of elements other than Mg, Zn and Ca)

[0028] The first region and the first electrode layer are biodegradable metals based on the chemical formula 1, and the second electrode layer may include a foreign substance with a higher standard reduction potential than the first electrode layer.

[0029] In addition, the second electrode layer may include at least one material selected from the group consisting of copper, zinc, silver, silver chloride, iron, and stainless steel.

[0030] The second region is a biodegradable metal according to Chemical Formula 1 and is electrically connected to a portion extending from the second electrode layer.

[0031] In addition, the second electrode layer may be based on the biodegradable metal of Chemical Formula 1, and the first electrode layer may include a foreign substance having a higher standard reduction potential than the second electrode layer.

[0032] Preferably, the microneedle has a length of 0.02 mm or more.

[0033] In addition, the carrier layer is sandwiched between the first electrode layer and the second electrode layer to form a stacked structure.

[0034] The first electrode layer and the second electrode layer are stacked in a state of being insulated from each other by an insulating layer, the second electrode layer has an opening portion so that at least a portion of the through portion of the first electrode layer is exposed, and the supporting layer covers at least a portion of the opening portion on the opposite side of the first electrode layer from the skin contact.

[0035] The through-hole formed in the first electrode layer is in the shape of a hole, and at least one of the microneedles is bent along the edge of the hole in a direction of contacting the user's skin.

[0036] In addition, the second electrode layer is in the form of a flexible cloth including conductive fibers.

[0037] In addition, the ion solution contains at least one selected from phosphate buffered saline and sodium chloride aqueous solution, and also contains at least one active ingredient of functional cosmetics and pharmaceuticals.

[0038] The active ingredient may be ionic.

[0039] In addition, the support layer can be selected from one or more of dry fabric-shaped materials, namely, pure cotton sheets, natural pulp sheets, and artificial fiber sheets.

[0040] In particular, the invention further includes a capsule for discharging the ionic solution to the supporting layer based on a user's starting action.

[0041] In addition, preferably, the area of ​​the first region is more than twice the area of ​​the second region.

[0042] In addition, the first region formed integrally with the first electrode layer is in the shape of a thin plate and has a thickness of 0.07 to 0.7 mm.

[0043] Effects of the Invention

[0044] The self-generating current skin patch containing a biodegradable metal of the present invention has the following effects based on the above-mentioned structure.

[0045] First, even if there is no separate power source such as a battery, sufficient effective ingredient ion electrophoresis and other microcurrent effects can be achieved by self-generating microcurrent.

[0046] Second, by using the magnesium-based biodegradable metal of Chemical Formula 1 of the present invention that is degradable upon contact with the skin or in tissue as the material of the skin contact electrode, the effective ingredient delivery effect caused by the decomposition product that acts as a drug delivery enhancer can be further improved.

[0047] Third, it also provides wrinkle improvement effects caused by byproducts and hydrogen generated during the decomposition process, reduces skin erythema caused by inflammation, and prevents skin damage caused by the sun.

[0048] Fourth, micro-scale microneedles are set at the user's skin contact point, which can penetrate the stratum corneum and make the transfer of active ingredients in the tissue smoother. In addition, the decrease in skin resistance caused by the microneedles will also increase electricity, thereby further improving the drug delivery effect based on ion electrophoresis.

[0049] Fifth, by appropriately arranging dissimilar metal materials electrically connected to the first and second areas in contact with the skin and having different standard reduction potentials, an appropriate product can be used according to the positive / negative ion properties of the active ingredient.

[0050] Sixth, biodegradable metals that come into contact with or are inserted into the skin produce electrochemical reactions, releasing more biodegradable metal ions and repairing the damaged skin barrier more quickly. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 is a side schematic diagram of a skin patch according to a preferred first embodiment of the present invention,

[0052] Figure 2 is a side schematic diagram of a skin patch according to a preferred second embodiment of the present invention,

[0053] Figure 3 is based on Figure 1 A side schematic diagram of a skin patch of the third embodiment, which is a modification of the first embodiment,

[0054] Figure 4 is a side schematic diagram of a skin patch of a preferred fourth embodiment of the present invention based on a built-in pre-filled capsule,

[0055] Figure 5 is a side schematic diagram of the overall structure of the skin patch of the present invention being attached to the skin via an adhesive sheet,

[0056] Figures 6a to 6h The present invention is a diagram showing a plurality of test pieces having compositions of biodegradable metals to which the present invention is applicable, on an alloy phase diagram.

[0057] Figure 7 This is an experimental schematic diagram of the electrodes used in the experiment of the present invention.

[0058] Figure 8 This is a schematic diagram of the experimental state in which copper and SUS301 are used as positive electrodes for comparison in PBS solution.

[0059] Fig. 9 This is a schematic diagram of the experimental state in which copper and SUS301 are used as positive electrodes for comparison in NaCl solution.

[0060] Fig.10 is a perspective view showing the shapes of the microneedles and the through-holes applicable to the first region of the present invention,

[0061] Fig.11 (a) to (c) are photographs of the prototype of the skin patch of the present invention in the case of no microneedles, the case of forming needles with a length of 100 μm, and the case of forming needles with a length of 230 μm, respectively.

[0062] Fig.12 This is a perspective view of a skin patch of the present invention in a productized form in which an adhesive sheet and a release paper are provided together.

[0063] Fig.13 yes Fig.12 The enlarged image of the patch product at the bottom.

[0064] Fig.14 is an exploded perspective view of a skin patch according to a preferred sixth embodiment of the present invention,

[0065] Fig.15 It is shown that Fig.14 The following is a photograph of the skin-attached state of the prototype of the skin patch of the embodiment.

[0066] Fig.16 The photographs from the left show chip samples in which a copper sheet, a 65 μm-thick Ag / AgCl coating on a PET film, and a 130 μm-thick Ag / AgCl coating on a PET film are used as the second electrode plate. DETAILED DESCRIPTION

[0067] Best Mode for Carrying Out the Invention

[0068] The advantages and features of the structure of the present invention and methods for achieving the same will be described below with reference to the accompanying drawings and multiple embodiments described in detail.

[0069] However, the present invention is not limited to the embodiments disclosed below, but will be presented in different various forms, and these embodiments are only for the purpose of complete disclosure of the present invention, and are used to fully inform the scope of the present invention to ordinary technicians in the technical field to which the present invention belongs. The present invention should be defined by the scope of the claims.

[0070] In the present invention, the part that basically contacts the user's skin is made of a conductive material other than a conductive metal material and consists of two or more regions separated from each other, and is therefore based on a structure that generates a microcurrent due to a potential difference generated between the two regions.

[0071] For this purpose, the patch of the present invention has the structure of the most basic battery, namely, the structure of a voltaic cell.

[0072] That is, a metal material having a high ionization tendency and easily becoming a positive ion (a material having a low standard reduction potential) is used as the negative electrode (-). In the present invention, a magnesium-based material is basically used, and the details are described later.

[0073] In addition, a conductive material with a low ionization tendency (a material with a high standard reduction potential) is used as the positive electrode (+), and an ion-exchangeable electrolyte is interposed between them.

[0074] In the present invention, the solution that acts as the electrolyte is called "ionic solution", which is carried by a carrying layer composed of dry fabric materials such as pure cotton sheets, natural pulp sheets, and artificial fiber sheets that can carry the solution.

[0075] That is, the metal of the negative electrode plate is ionized into positive ions and releases electrons through the ionic solution carried by the supporting layer. At the same time, the released electrons move to the positive electrode plate through human tissue, generating a microcurrent. The current generated at this time acts as an electrolyte, rapidly and deeply transferring the active ingredients in the ionic solution containing the active ingredients into the subcutaneous tissue.

[0076] During the penetration and diffusion process of the ion solution, the active ingredients penetrate and diffuse into the subcutaneous tissue, or they have positive or negative ionic properties and are directly promoted to move through the action of electricity.

[0077] That is, by providing an active ingredient with negative ions when the negative electrode metal is in contact with the skin, or by providing an active ingredient with positive ions when the positive electrode metal is in contact with the skin, the transmission and diffusion effects of the active ingredients based on electricity can be maximized. To this end, the present invention mainly illustrates two forms of embodiments and corresponding variations, and proposes other additional embodiments.

[0078] Figure 1This is a side schematic diagram of a self-generated current skin patch containing a biodegradable metal based on a preferred first embodiment of the present invention, wherein a first electrode layer 11 constituting a first area 10 in contact with the user's skin and serving as a negative electrode has a magnesium-based composition represented by the chemical formula 1 of the present invention described later, and a second electrode layer 22 in which a carrier layer 30 is interposed between the first electrode layer 11 is composed of a material having a lower ionization tendency and a higher standard reduction potential than that of the first electrode layer 11, such as copper, zinc, silver, silver chloride, iron, stainless steel, etc.

[0079] In this state, the first region 10 and the second region 20 extending from the second electrode layer 22 are in contact with the user's skin, and when the supporting layer 30 sandwiched between the first electrode layer 11 and the second electrode layer 22 which are in an electrically insulated state due to the supporting layer 30 carries an ion solution that acts as an electrolyte, ionization of the metal in the first electrode layer occurs, and electrons move through the skin, thereby generating current.

[0080] If the active ingredient contained in the ionic solution of the carrier layer 30 has negative ions, the active ingredient supplied to the skin below the first region 10 through the through-holes 16 can be transferred and diffused more effectively based on ion electrophoresis.

[0081] On the contrary, if the effective component in the ionic solution has positive ions, preferably, the difference in standard reduction potential between the first electrode layer 11 and the second electrode layer 22 is opposite to that in the first embodiment.

[0082] Right now, Figure 2 This is a side schematic diagram of a self-generated current skin patch containing a biodegradable metal based on a preferred second embodiment of the present invention. Unlike the first embodiment, the first electrode layer 11 constituting the first area 10 in contact with the user's skin acts as a positive electrode, and the second electrode layer 22 having a magnesium-based composition represented by the chemical formula 1 of the present invention described later is composed of a material with a low ionization tendency and a high standard reduction potential, such as copper, zinc, silver, silver chloride, iron, stainless steel, etc.

[0083] In this state, if the active ingredient contained in the ionic solution of the supporting layer 30 has positive ionization, the transfer and diffusion of the active ingredient supplied to the lower part of the first region 16 through the through-hole 16 based on ion electrophoresis is more effective than the case of the active ingredient having electrically neutral or negative ionization.

[0084] In order to clearly distinguish the two types, in the present invention, the first embodiment is named as the basic type and the second embodiment is named as the reverse type.

[0085] As a modification of the first embodiment, it is possible to provide Figure 3 Patch shown.

[0086] In the first embodiment as a basic type, since the second region 20 has a structure in which only the portion extending from the second electrode layer 22 directly contacts the skin, in this embodiment, the second region 20 functions only as an electrode required for ion electrophoresis and microcurrent.

[0087] However, the basic type and Figure 3 When the second electrode layer 22 having a positive electrode effect as shown in the third embodiment is bonded to the second region 20 with a biodegradable metal having a magnesium-based composition as shown in the chemical formula 1 described later, the beneficial effects obtainable in the metal decomposition process can be obtained over the entire area of ​​the patch.

[0088] In addition, the following explains Figure 4 The structure of the self-generated current skin patch containing biodegradable metal based on the fourth embodiment of the present invention.

[0089] As described above, in a state where the supporting layer 30 of the present invention does not contain any ion solution, an ion solution containing an active ingredient may be supplied through the through-hole 16 or the side surface of the first region 10 .

[0090] That is, in this case, the patch of the present invention and an ampoule containing an active ingredient are separately provided in a set form, and the user can allow the support layer 30 to absorb the solution in the ampoule before applying the patch to the skin.

[0091] However, in order to eliminate such inconvenience in use, the patch of the fourth embodiment, which is a variation of the third embodiment as the basic type, has a separate capsule 40 contained in or arranged adjacent to the volume of the carrier layer 30, and has a structure in which an ionic solution containing an active ingredient is stored in the capsule 40.

[0092] In this case, the user may discharge the ion solution in the capsule 40 into the supporting layer 30 by pulling the handle 41 connected to the capsule 40 .

[0093] The patch of the present invention shown in the first to fourth embodiments is as follows Figure 5 As shown, the adhesive sheet 50 can be attached to the user's skin, and as shown in FIG. Fig.12 and Fig.13 As shown, the adhesive sheet 50 and the release paper are provided together in a product form.

[0094] Fig.13 yes Fig.12The enlarged view of the patch product at the lower end is shown in a transparent state in order to clarify the positional relationship between the components. The first region 10 formed by multiple through-holes 16 and a wide area is formed by the first electrode layer 11, and a portion of the second electrode layer 22 arranged in a state of sandwiching the carrier layer 30 with the first electrode layer 11 extends to the right from the position overlapping with the first region 10, and the extension portion is bonded to the microneedle sheet corresponding to the second region 20 having a narrower area than the first region 10.

[0095] In this case, the first electrode layer 11 and the first region 10 of Example 1, the second electrode layer 22 and the second region 10 of Example 2, and the first electrode layer 11, the first region 10 and the second region 20 of Example 3 may be applied with the biodegradable metal of the present invention.

[0096] The biodegradable metal of the present invention is defined by the above Chemical Formula 1.

[0097] [Chemical formula 1]

[0098] Mg a Zn b Ca c X d

[0099] In the chemical formula 1, a, b, c and d are the weight % of each component, a+b+c+d=100 weight %, a is the largest, and therefore has a value greater than 0 and less than 100, 0≤b≤5, 0≤c≤1, 0≤d≤1, and X is one or more impurity groups selected from elements other than Mg, Zn, and Ca.

[0100] That is, the biodegradable metal of the present invention includes metals that react with water in the body to decompose, but specifically, magnesium is used as a main component, zinc and calcium are mixed in an appropriate ratio so as to be harmless to the human body and have beneficial effects, and can be selected from compositions having various alloy phases and decomposition rates.

[0101] Figure 6a to Figure 6h The internal phase of the alloy based on the content of magnesium, zinc and calcium at a specific temperature is shown. Depending on their content, the alloy exists in the form of α-magnesium phase (HCP), ternary phase (Ca2Mg6Zn3), Mg2Ca (C14_b), MgZn, etc. Among them, the Mg2Ca phase can improve the strength of the alloy, but it forms a galvanic circuit and increases the decomposition rate, and the MgZn phase also induces microgalvanic in the alloy and increases the decomposition rate. That is, if the decomposition rate increases, it means that the degree of ionization is higher than that of pure Mg, so the electromotive force caused by the difference in standard reduction potential with the positive electrode layer will also increase.

[0102] When the casting temperature is above about 650°C, as the alloy in the liquid state cools, it passes through the "α magnesium phase (HCP) + Liquid phase coexistence area", "α magnesium phase (HCP) generation area", "α magnesium phase (HCP) and ternary phase (Ca2Mg6Zn3) generation area", at which time the structure of the alloy is determined by the generated α magnesium phase (HCP) and ternary phase (Ca2Mg6Zn3), preventing the generation of the MgZn phase at its lower end. If the MgZn phase is to be intentionally generated using the composition of test piece 3, it is necessary to heat treat the manufactured alloy for a long time at a temperature below about 120°C. In a general casting furnace, it is necessary to take it out of the casting furnace and cool it rapidly before cooling to the temperature at which the MgZn phase is generated, so that the MgZn phase will not be generated.

[0103] In addition, regarding the above-mentioned impurities, Ce, Mn, Al, Pb, Fe, Ni, Zr, Cu, Th, Be, Cd, Sn, P, Si, La, Sr, Pr, Na and Y, etc., flow into from a crucible during the manufacturing process, and preferably, the total amount is less than 1 weight%.

[0104] In the present invention, the biodegradable metal can be produced by melting and mixing magnesium, calcium and zinc and then forming them as is generally known.

[0105] The melting can be carried out in an inert gas atmosphere such as argon (Ar) that does not react with magnesium, calcium and zinc, or in a vacuum atmosphere, and various methods can be used, such as a resistance heating method that generates heat by supplying electricity to a resistor, a heating method that generates current through an induction coil, or a laser or focusing method.

[0106] For example, the forming may be a cooling method, an extrusion method, a metal processing method, etc., but is not limited thereto. The cooling method may be used to improve the mechanical strength of the magnesium alloy. In more detail, a method of immersing a crucible containing molten magnesium in water may be used. In addition, a cooling method of spraying molten magnesium with an inert gas such as argon may be used. The above-mentioned spray cooling method has a very fast cooling rate and can show a very fine structure. However, if magnesium is cast in a small size, a plurality of pores may be formed inside, so be careful.

[0107] The above-mentioned processing method is used to manufacture a magnesium-based alloy having a composition and a crystalline phase form suitable for generating a desired level of electromotive force. For example, while using the same electrode, a galvanic circuit is formed in a scheme to further increase the electromotive force, thereby increasing the decomposition rate and forming an alloy containing a stronger Mg2Ca phase.

[0108] Specific ways to implement the invention

[0109] [Manufacturing of biodegradable metal test pieces]

[0110] According to the composition of Table 1 below, calcium, zinc and magnesium are loaded into a crucible with an inner diameter of 50 mm made of stainless steel (SUS 410) (or a carbon crucible). Subsequently, in order to prevent the calcium, zinc and magnesium in the crucible from contacting with the air, the crucible temperature is raised from about 700°C to about 750°C by a resistance heating furnace while argon gas flows around the crucible, so that the calcium, zinc and magnesium are melted. The materials in the crucible are stirred so that the molten calcium, zinc and magnesium are fully mixed with each other. The completely molten magnesium alloy is cooled to produce a solid magnesium alloy. In addition, during cooling, in order to improve the mechanical strength of magnesium, the crucible is immersed in water to rapidly cool the molten magnesium alloy.

[0111] The solid magnesium alloy was extruded to produce a test piece, the extrusion temperature was 400°C, and the cross-sectional area reduction ratio before and after extrusion (extrusion ratio) was set to 40: 1. The composition of the produced test piece was evaluated by a metal component analysis device (SPECTRO MAXx), and the results are shown in Figures 6(a) to (h) and Table 1.

[0112]

Table 1

[0113]

[0114]

[0115] Subsequently, the manufactured test piece was placed in a heating furnace and further heat-treated at 450° C. for 24 hours to manufacture a heat-treated biodegradable metal test piece.

[0116] [Evaluation of Decomposition Characteristics of Biodegradable Metals]

[0117] Some samples of the heat-treated biodegradable metal test pieces prepared as above were selected to evaluate the degradation characteristics. Evaluation of Decomposition Characteristics Considering the characteristics of alkaline earth metals that release hydrogen when decomposing, the amount of hydrogen released during decomposition was measured using an Eudiometer in a PBS solution set at 37°C. The results are shown in Table 2.

[0118]

Table 2

[0119]

[0120]

[0121] As can be seen from Table 2, by comparing the commonly used biodegradable alloy material as a comparative example with the test piece manufactured in the embodiment, it can be confirmed that test pieces with higher decomposition rates and lower decomposition rates exist in various ranges based on the commonly used biodegradable alloy material. Therefore, according to the effective ingredients, applicable time, etc. of the skin patch provided by the present invention, a magnesium-based alloy composition with an appropriate decomposition rate can be selectively applied.

[0122] Because the microneedles 15 formed in the user skin contact portion of the present invention, i.e., the first area 10 or the second area 20, are made of a biodegradable metal having a composition represented by the chemical formula 1, they are different from ordinary microneedles. After being inserted into the subcutaneous tissue or epithelium for the injection of active ingredients, they act as electrodes while being absorbed and decomposed to release metal ions and decomposition products into the body.

[0123] Magnesium (Mg), calcium (Ca), zinc (Zn), etc. used as materials of the microneedles of the present invention are biodegradable metals of the alkaline earth metal series, and as shown in the following formula, they have a mechanism of reacting with water to release hydrogen. Therefore, the microneedles made of the metals release ions and decomposition products when absorbed and decomposed subcutaneously, and the hydrogen produced by the byproducts produces a swelling effect under the skin, thereby having the effect of improving wrinkles and reducing the skin erythema caused by inflammation, and preventing skin damage caused by the sun. (YOON, KS et al., Histological study on the effect of electrolyzed reduced water-bathing on UVB radiation-induced skin injury in hairless mice, Biological and Pharmaceutical Bulletin 34, 1671-7, 2011; IGNACIO, RM, et al., The balneotherapy effect of hydrogen reduced water on UVB-mediated skin injury in hairless mice, Molecular & Cellular Toxicology 9, 15-21, 2013)

[0124] Mg+2H2O→Mg(OH)2+H2(gas)

[0125] Zn+2H2O→Zn(OH)2+H2(gas)

[0126] Ca+2H2O→Ca(OH)2+H2(gas)

[0127] In addition, the byproducts ZnO and MgCl generated by the insertion of magnesium (Mg) and zinc (Zn) into the organism will not penetrate into the subcutaneous tissue, but will remain on the skin surface, and can also act as a drug delivery enhancer to improve drug absorption. Therefore, the needle made of biodegradable metal can further improve the delivery effect of the active ingredient carried by the patch of the present invention.

[0128] Therefore, as described above, by applying the biodegradable metal to the skin contacting part of the skin patch of the present invention, a synergistic effect such as the beneficial effect caused by the decomposition product and the effect as a drug delivery enhancer can be obtained.

[0129] [Electromotive force generation experiment based on the type of electrolyte and the type of metal of the positive electrode]

[0130] Prior to this experiment, as a preliminary experiment, the generation of electromotive force in PBS and commercial acne ampoule solution on the market was compared, but the electromotive force of the acne ampoule solution in any positive electrode metal did not meet the standard. Therefore, it was confirmed that the ion solution applicable to the present invention should be used in a state where a highly ionized solution as an electrolyte and an active ingredient are mixed with each other, or an aqueous solution of the active ingredient with a high ionization degree should be used.

[0131] like Figure 7 As shown, a pure Mg electrode containing inevitable impurities was used as the negative electrode, a commercial product phosphate buffered saline (PBS) was prepared as an electrolyte suitable for the ion solution of the present invention, and an artificially prepared 0.9% NaCl aqueous solution was prepared, and experiments were conducted using a type of stainless steel - SUS301 and copper as the positive electrode metal.

[0132] This experimental reference Figures 8 to 9 Photos.

[0133] Figure 8 The following is an experimental comparison of copper and SUS301 as positive electrodes in a PBS solution.

[0134] Fig. 9 The following is an experimental state in which copper and SUS301 are used as positive electrodes in a NaCl solution for comparison.

[0135] The resulting results are shown in Table 3.

[0136]

Table 3

[0137]

[0138]

[0139] The operating voltage and current were measured in combination with the open circuit voltage Voc using a 500Ω resistor. The results confirmed that the artificially prepared 0.9% NaCl aqueous solution was more conducive to the electrolyte that an ion solution should contain than PBS. This is presumably because there are fewer factors in the aqueous solution that interfere with ion movement.

[0140] On the other hand, the overall match as a positive electrode shows that the Mg-SUS301 combination is more advantageous in terms of electromotive force, but it is predicted that the Mg-Cu combination may also be sufficient for application to the patch of the present invention. In the human body application experiment described later, copper is more advantageous in terms of ductility related to skin fit and adhesion, so it can be appropriately selected according to the structure of the patch to be manufactured, etc.

[0141] Through the experiments, the ionic solution of the present invention preferably includes other ionic aqueous solutions with similar ionization degree including NaCl aqueous solution. Therefore, as the ionic solution of the present invention, an effective ingredient solution with a comparable self-ionization degree can be used or the good electrolyte solution and the effective ingredient can be mixed and used.

[0142] The active ingredient is not limited as long as it can exert the effect of functional cosmetics or medicines, but an ionic active ingredient is preferred.

[0143] For example, the definition of functional cosmetics is as follows.

[0144] -Functional cosmetics that help whiten your skin

[0145] -Functional cosmetics that help improve skin wrinkles

[0146] -Functional cosmetics that help protect the skin from UV damage

[0147] -Functional cosmetics that help change hair color (including desalination and bleaching)

[0148] -Functional cosmetics that help remove body hair

[0149] -Functional cosmetics that help relieve acne-prone skin

[0150] In particular, regarding the skin whitening (brightening skin tone) function, the function of improving skin wrinkles, and the function of relieving acne, the applicant of the present invention has disclosed through the gazettes of Patent Registration No. 2194089 "Flexible metal patch with antioxidant activity and whitening effect and method of use thereof" and Patent Registration No. 2310566 "Patch for relieving acne and prevention", etc., that the biodegradable metal of the present invention itself exhibits the above-mentioned functional effects even without other active ingredients. Therefore, if an active ingredient for this purpose and the biodegradable metal skin patch of the present invention are used, a higher synergistic effect can be achieved.

[0151] In addition, if Fig.10 As shown, in the microneedles 15 and the through-holes 16 applied to the first region 10 according to the present invention, the through-holes 16 are formed in the shape of polygonal or closed curve holes, and at least one microneedle 15 is arranged at the edge of the through-holes 16 .

[0152] The advantage of this structure is that in the manufacture of the microneedle patch, the microneedles and the through-portions are formed simultaneously on a plane, and then the microneedles are bent with a clamp or the like, so that a patch formed with multiple microneedles can be easily obtained, and in use, the microneedles are arranged around the wider through-portions, so that the active ingredients supplied from the upper side of the through-portion 16 can be easily transferred to the bottom through the through-portion 15, and in particular, can be simultaneously transferred to the inside of the skin along the insertion path of the microneedles.

[0153] That is, according to the patch of the present invention, since the effective ingredients in the ion solution carried in the carrying layer are transferred to the inside of the skin through the above process and can diffuse rapidly under the action of electricity, the structure of the microneedle 15 and the through-hole 16 can be applied in a structure more suitable for the present invention.

[0154] In addition, in addition to the aforementioned beneficial effects produced by decomposition when inserted into the skin, the microneedle 15 of the present invention can also generate a higher electromotive force according to the main purpose of the present invention, and play a decisive role in providing a product in a practical form in which the ion electrophoresis of the active ingredient is not just a concept.

[0155] [Electromotive force experiment based on the presence and length of microneedles attached to the skin]

[0156] Fig.11 (a) to (c) are photographs of the prototype of the self-generated current skin patch containing a biodegradable metal of the present invention in the case of no microneedles, the case of forming microneedles with a length of 100 μm, and the case of forming microneedles with a length of 230 μm.

[0157] As shown in the photo, the first electrode layer whose entire area contacts the skin uses a 0.07mm thick magnesium metal sheet with multiple porous through-portions, the second electrode layer which partially contacts the skin uses a 0.07mm copper metal sheet, and the carrying layer of the ion solution uses a 0.28mm pure cotton sheet.

[0158] The first electrode layer and the second electrode layer are electrically insulated and isolated structures without direct electrical connection due to the pure cotton sheet, and a 0.9% NaCl aqueous solution is used as the electrolyte of the ion solution.

[0159] In this state, the Fig.11 The patches are applied to the user's human skin respectively, and the working voltage and working current are measured, and the results are shown in Table 4 below.

[0160]

Table 4

[0161] Patches <![CDATA[V L [V]]> <![CDATA[I L [mA]]> <![CDATA[P L [μW]]]> (a) 1.487 0.115 0.171 (b) 1.417 0.326 0.461 (c) 1.434 1.935 2.774

[0162] That is, compared with (a) without microneedles, it can be confirmed that the patches (b) and (c) show a significant increase in electromotive force as the current increases, and in particular, the electromotive force of (c) increases by nearly 6 times compared with (b). Therefore, when the needle length exceeds 100 μm and penetrates the stratum corneum and epidermis of the skin and reaches the dermis, it is estimated that an extreme skin resistance reduction effect can be obtained, so the thickness of the microneedle is preferably the usual epidermal thickness of 50 μm or more.

[0163] In particular, as applicable to the patch manufacturing of this experiment, the thinner the thickness of the thin plate in the first or second area, the better the close contact and adhesion to the skin, so its thickness is preferably within an appropriate range. In particular, in the biodegradable metal of the present invention, it is not easy to process a thin plate of less than 0.07 mm, and when it is above 0.7 mm, even if it has ductility, the phenomenon of lifting on the skin can be confirmed. The preferred range is 0.07 to 0.7 mm.

[0164] In addition, through various experiments, it can be confirmed that the larger the volume of the supporting layer 30 carrying the ion solution, that is, the greater the amount of electrolyte solution, the greater the increase in the electrical physical quantity. According to the aforementioned embodiment of the present invention, the patch product having a structure in which the supporting layer is sandwiched between the first electrode layer and the second electrode layer has limitations in increasing the thickness of the supporting layer. Therefore, it is best to maximize its area. Preferably, the area of ​​the first region 10 corresponding to the area of ​​the supporting layer 30 is more than twice that of the second region 20.

[0165] In this regard, as another variation of the third embodiment of the basic type, Fig.14 The sixth embodiment is shown.

[0166] The drawing is an exploded perspective view showing that the first area 10 and the second area 20 as the skin contact side are arranged in the upper part of the drawing, and in the lower part, the second electrode layer 22, the carrier layer 30, etc. are arranged in sequence according to the stacking order.

[0167] That is, the first region 10 and the second region 20 can be composed of a biodegradable metal having a magnesium-based composition having the chemical formula 1 described later. On the other hand, the second region 20 is electrically connected to the material forming the second electrode layer 22, while the first region adopts a structure combined with an insulating layer 60 to prevent direct electrical contact with the second electrode layer 22.

[0168] That is, this integrated structure of the insulating layer 60 and the second electrode layer 22 can be manufactured by coating a conductive material on one surface of an insulating film (PET film, etc.) to form the second electrode layer 22 and then removing the insulating film in a partial area, or it can be manufactured to include conductive fibers (copper fibers, silver fibers, etc.), and the first area 10 is laminated and bonded to an insulating layer 60 formed by combining an insulating bonding means on a partial area of ​​one side of a conductive cloth.

[0169] in other words, Fig.14 The structure shown is as follows: after the silver cloth woven with silver fibers is cut into a corresponding shape as the material of the second electrode layer 22, an insulating adhesive is applied to a part of one side of the cloth or an insulating tape is combined to form Fig.15 The insulating layer 60 represented in white is combined with the biodegradable metal corresponding to the second area 20 in the black part directly exposed on the surface of the second electrode layer 22, and the biodegradable metal corresponding to the first area 10 in the white part insulated in the second electrode layer 22 is combined with the first electrode layer 11.

[0170] In addition, unlike the structure in which the carrier layer 30 is sandwiched between the first electrode layer 11 and the second electrode layer 22, that is, the previous embodiment, Fig.14 In the illustrated embodiment, the carrier layer 30 is located outside the second electrode layer 22 (lower side in the figure, opposite to the skin attachment surface). When attached to the skin for use, the carrier layer 30 is located on the outermost side.

[0171] The advantage of this structure is that, compared with the structure in which the carrier layer 30 is sandwiched between pure cotton sheets, natural pulp sheets, artificial fiber sheets, etc., the first electrode layer 11 and the second electrode layer 22 in the form of a thin film are first stacked, and then the carrier layer is combined to the outside. Therefore, it is not only easy to manufacture, but also helps to ensure the area of ​​the carrier layer 30, and the durability in the product state also becomes excellent.

[0172] In particular, as in the above-mentioned structure, in a structure in which there is no carrier layer for the ionic solution between the first electrode layer 11 and the second electrode layer 22, in order to start generating self-generated current when the patch is attached without supplying the ionic solution in advance, the second electrode layer 22 should also be a structure open to the upper direction and having an opening portion 65, etc. For this purpose, the second electrode layer 22 preferably has an opening portion 65, so that the ionic solution can be easily and continuously supplied to the first area 10 and the skin thereunder without being limited by the supply amount.

[0173] At this time, by further combining the supporting layer 30 in the form of covering at least a portion (as much as possible all) of the opening 65, the ionic solution supplied from the top instantly diffuses to the entire area of ​​the supporting layer 30, and the electrochemical reaction occurs more smoothly. The carried ionic solution can be slowly and constantly supplied to the interior of the patch, so that ion exchange can also be achieved between the exposed part of the electrically insulating second electrode layer 22 and the first electrode layer 11 through the electrolysis of the ionic solution.

[0174] According to the above structure, as in the first to fourth embodiments, if the carrier layer 30 is fixedly sandwiched between the first electrode layer 11 and the second electrode layer 22, it is possible to solve the problem of limited area of ​​the carrier layer 30, the problem of moisture leaking from the carrier layer weakening skin adhesion due to the carrier layer 30 being located on the inner side of the patch, the problem that the ionic solution is not easy to diffuse to the entire surface of the first electrode layer 11, etc., and it also has additional advantages, such as acting as a filter that can filter out foreign matter in the ionic solution.

[0175] The patch of the sixth embodiment is actually attached to the skin. Fig.15 The photographs show that, through the structure described above, it can be confirmed that when the self-generated current skin patch containing a biodegradable metal of the present invention is attached to the skin, the structure of the ion solution containing the active ingredient can be smoothly and continuously supplied through the top supporting layer 30.

[0176] [Evaluation of the characteristics of patches containing Ag / AgCl mixed electrode materials]

[0177] After the electromotive force experiment in the combination of magnesium metal as the first electrode layer and Cu or SUS301 as the second electrode layer confirmed previously, combined with the characteristic evaluation of the patch structure that can easily realize the structure of the above-mentioned embodiment 6, a magnesium metal thin plate with a thickness of 0.07 mm containing inevitable impurities was prepared as the first electrode layer, two electrode layers prepared by applying a paste Ag / AgCl mixture on a PET film with a thickness of 0.05 mm were prepared as the second electrode layer, and a Cu thin plate with a thickness of 0.03 mm was prepared as a comparative sample, and three samples were prepared in which the first electrode layer and the second electrode layer were laminated and combined in an insulated state. The morphology of the sample is as follows: Fig.16 As shown, it has the characteristics shown in the following Table 5 from the left.

[0178]

Table 5

[0179]

[0180] The paste Ag / AgCl mixture used in the experiment is SC141 sold by KATIE Co., Ltd., which has the condition of solidifying when heated at 120°C for 30 minutes. Therefore, the Ag / AgCl mixture was coated on a 50μm PET film with different thicknesses for the experiment. The results of the experiment with the above sample under a load resistance of 500Ω are shown in Table 6 below. The applicable electrolyte solution is a 0.9% NaCl aqueous solution.

[0181]

Table 6

[0182]

[0183] Compared with the experimental results of the Cu sheet, Sample 1, Ag / AgCl has a further improvement effect. From the results of Samples 2 and 3, it can be seen that as the thickness of the Ag / AgCl coating increases, the operating voltage, operating current and electromotive force increase proportionally, but when the second electrode layer + insulating layer structure is presented in the form of a coating on the film, it has an appropriate thickness in terms of fracture or flexibility. From the results, compared with Cu, when Ag is used as the material of the second electrode layer, it has electrical advantages, and using silver cloth made of silver fibers as the second electrode layer instead of using a coating method can produce products with advantages in flexibility and adhesion of the patch.

[0184] Although specific embodiments of the present invention have been described so far, various modifications may be made without departing from the scope of the present invention.

[0185] Therefore, the scope of the present invention should not be limited to the above-described embodiments, but should be determined based on the following claims and their equivalents.

Claims

1. A self-generated current skin patch containing a biodegradable metal, characterized in that: include: a first area (10) in contact with the user's skin and a second area (20) spaced from the first area (10) and in contact with an adjacent area of ​​the skin in contact with the first area (10), The first region (10) or the second region (20) includes a biodegradable metal that can be decomposed and absorbed by contacting the user's skin or reacting with moisture in the tissue; A first electrode layer (11) is formed integrally with the first region (10) in a thin sheet form directly contacting the user's skin and having at least one through portion for transmitting fluid from the side opposite to the skin contact; A second electrode layer (22) is formed of a different material having a standard reduction potential different from that of the material forming the first electrode layer (11), is insulated from the first electrode layer (11), is located on the side of the first electrode layer (11) opposite to the skin contact side, and at least a portion thereof is extended and electrically connected to the second region (20); The carrying layer (30) is in the form of a sheet with thickness and is located on the side of the first electrode layer (11) opposite to the skin contact side, and is made of a hydrophilic material capable of carrying an ion solution.

2. The self-generated current skin patch containing biodegradable metal according to claim 1, characterized in that: The first area (10) or the second area (20) includes at least one microneedle (15) protruding in a direction of contact with the user's skin.

3. The self-generated current skin patch containing biodegradable metal according to claim 1 or 2, characterized in that: The biodegradable metal is represented by the following chemical formula 1: [Chemical formula 1] Mg a Zn b Ca c X d In Chemical Formula 1, a, b, c and d are weight % of each component, a+b+c+d=100 weight %, a is the largest, 0≤b≤5, 0≤c≤1, 0≤d≤1, and X is one or more of an impurity group consisting of elements other than Mg, Zn and Ca.

4. The self-generated current skin patch containing biodegradable metal according to claim 3, characterized in that: The first region (10) and the first electrode layer (11) are biodegradable metals based on the chemical formula 1, and the second electrode layer (22) includes a foreign substance having a higher standard reduction potential than the first electrode layer (11).

5. The self-generated current skin patch containing biodegradable metal according to claim 4, characterized in that: The second electrode layer (22) comprises one or more substances selected from the group consisting of copper, zinc, silver, silver chloride, iron, and stainless steel.

6. The self-generated current skin patch containing biodegradable metal according to claim 5, characterized in that: The second region (20) is a biodegradable metal based on Chemical Formula 1, and is electrically connected to a portion extending from the second electrode layer (22).

7. The self-generated current skin patch containing biodegradable metal according to claim 3, characterized in that: The second electrode layer (22) is a biodegradable metal based on the chemical formula 1, and the first electrode layer (11) includes a foreign substance having a higher standard reduction potential than the second electrode layer (22).

8. The self-generated current skin patch containing biodegradable metal according to claim 2, characterized in that: The microneedle (15) has a length of 0.02 mm or more.

9. The self-generated current skin patch containing biodegradable metal according to claim 1, characterized in that: The carrier layer (30) is sandwiched between the first electrode layer (11) and the second electrode layer (22) to form a stacked structure.

10. The self-generating current skin patch containing biodegradable metal according to claim 1, characterized in that: The first electrode layer (11) and the second electrode layer (22) are stacked in a state of being insulated from each other by an insulating layer (60), The second electrode layer (22) has an opening (65) to expose at least a portion of the through portion of the first electrode layer (11). The carrier layer (30) covers at least a portion of the opening (65) on the opposite side of the first electrode layer (11) from the skin contact side.

11. The self-generated current skin patch containing biodegradable metal according to claim 2, characterized in that: The through-portion formed in the first electrode layer (11) is in the shape of a hole, and at least one of the microneedles (15) is bent along the edge of the hole in a direction of contact with the user's skin.

12. The self-generated current skin patch containing biodegradable metal according to claim 4, characterized in that: The second electrode layer (22) is in the form of a flexible cloth containing conductive fibers.

13. The self-generating current skin patch containing biodegradable metal according to claim 1, characterized in that: The ion solution comprises at least one selected from phosphate buffered saline and sodium chloride aqueous solution.

14. The self-generated current skin patch containing biodegradable metal according to claim 1 or 13, characterized in that: The ion solution also includes at least one of the active ingredients of functional cosmetics and medicines.

15. The self-generating current skin patch containing biodegradable metal according to claim 14, characterized in that: The active ingredient is ionic.

16. The self-generating current skin patch containing biodegradable metal according to claim 1, characterized in that: The bearing layer (30) is selected from one or more of dry fabric-shaped materials, namely, pure cotton sheets, natural pulp sheets, and artificial fiber sheets.

17. The self-generated current skin patch containing biodegradable metal according to claim 1 or 16, characterized in that: Also included is a capsule (40) that discharges the ion solution to the supporting layer (30) based on a user's starting action.

18. The self-generating current skin patch containing biodegradable metal according to claim 9, characterized in that: The area of ​​the first region (10) is at least twice the area of ​​the second region (20).

19. The self-generating current skin patch containing biodegradable metal according to claim 1, characterized in that: The first region (10) formed as a whole with the first electrode layer (11) is in the shape of a thin plate and has a thickness of 0.07 to 0.7 mm.

Citation Information

Patent Citations

  • Microcurrent-generating patch

    KR101423241B1

  • Transdermal drug delivery self generated microcurrent patch and manufacturing method thereof

    KR102390735B1